Cilostazol Ameliorates Peripheral Neuropathic Pain in Streptozotocin-Induced Type I Diabetic Rats - Cheng, Kuang-I.; Wang, Hung-Chen; Tseng, Kuang-Yi; Wang, Yi-Hsuan; Chang, Chung-Yu; Chen, Yi-Jing; Lai, Chung-Sheng; Chen, Dar-Ren; Chang, Lin-Li (Frontiers in Pharmacology, 2022)
Background: Cilostazol is an antiplatelet agent with vasodilating, endothelial function restoration, and anti-inflammatory effects. This study aims to investigate the efficacy of oral cilostazol for preventing the development of diabetic peripheral neuropathy (DPN). Materials and Methods: Ninety adult male Sprague-Dawley rats were divided into five groups: (1) naïve (control); (2) diabetic (DM); (3) DM receiving 10 mg/kg cilostazol (cilo-10); (4) DM receiving 30 mg/kg cilostazol (cilo-30); and (5) DM receiving 100 mg/kg cilostazol (cilo-100). Hindpaw responses to thermal and mechanical stimuli were measured. Activation of microglia and astrocytes in the spinal dorsal horn (SDH) and expression of NaVs in the dorsal root ganglia (DRG) were examined with Western blots and immunofluorescence. Results: DM rats displayed decreased withdrawal thresholds to mechanical stimuli (mechanical allodynia) and blunted responses to thermal stimuli. In addition, the expression of microglia increased, but astrocytes were reduced in the SDH. Upregulation of Nav-1.1, 1.2, -1.3, -1.6, and -1.7 and downregulation of Nav-1.8 were observed in the DRG. The DM rats receiving cilostazol all returned to their DM-induced decrease in withdrawal threshold to mechanical stimuli and attenuated neuropathic pain. Additionally, all cilostazol treatments suppressed the level of activated microglial cells and ameliorated the DM-induced decline in astrocyte expression levels in the SDH. However, only the rats treated with cilo-100 demonstrated significant improvements to the aberrant NaV expression in the DRG. Conclusions: Oral cilostazol can blunt the responses of mechanical allodynia and has the potential to treat diabetic neuropathy by attenuating NaV and glial cell dysregulation.